SECURE PCI: how important can a subgroup analysis be? - Kerneis, Mathieu; Yee, Megan K.; Gibson, C. Michael (Journal of Thoracic Disease, 2018)
Among acute coronary syndrome (ACS) and stable coronary artery disease patients, the effect of a loading dose of statin, prior to revascularization, has been assessed in several observational studies and randomized controlled trials (1-3). A high dose of statin before percutaneous or surgical revascularization was associated with a decreased risk of periprocedural myocardial infarction (MI), contrast induced—acute kidney injury and, finally, improved clinical outcomes (4,5). The underlying mechanism was hypothesized to be related to the complex pleiotropic effects of statins which improve endothelial function, stabilize the atherosclerotic plaque, and decrease the vascular inflammation (6).